Signaling through MAP kinase networks in plants - Sanan Mishra, N.; Tuteja, R.; Tuteja, N.
Protein phosphorylation is the most important mechanism for controlling many fundamental cellular processes in all living organisms including plants. A speciWc class of serine/threonine protein kinases, the mitogen-activated protein kinases (MAP kinases)play a central role in the transduction of various extra- and intracellular signals and are conserved throughout eukaryotes. These generally function via a cascade of networks, where MAP kinase (MAPK)is phosphorylated and activated by MAPK kinase (MAPKK), which itself is activated by MAPKK kinase (MAPKKK). Signaling through MAP kinase cascade can lead to cellular responses including cell division, diVerentiation as well as response to various stresses. In plants, MAP kinases are represented by multigene families and are organized into a complex network for eYcient transmission of speciWc stimuli. Putative plant MAP kinase cascades have been postulated based on experimental analysis of in vitro interactions between speciWc MAP kinase components. These cascades have been tested in planta following expression of epitope-tagged kinases in protoplasts. It is known that signaling for cell division and stress responses in plants are mediated through MAP kinases and even auxin, ABA and possibly ethylene and cytokinin also utilize a MAP kinase pathway. Most of the biotic (pathogens and pathogen-derived elicitors)including wounding and abiotic stresses (salinity, cold, drought, and oxidative)can induce defense responses in plants through MAP kinase pathways. In this article we have covered the historical background, biochemical assay, activation/inactivation, and targets of MAP kinases with emphasis on plant MAP kinases and the responses regulated by them. The cross-talk between plant MAP kinases is also discussed to bring out the complexity within this three-component module.
Keywords: ABIOTIC STRESS; BIOTIC STRESS; CELL DIVISION; MAP KINASE; PHYTOHORMONES; PHOSPHORYLATION; SIGNAL TRANSDUCTION